Selected Factors Influencing the Social and Environmental Aspects of Sustainability of SMEs - Dvorsky, Jan; Kubalek, Jan; Barinova, Dagmar; Androniceanu, Armenia; Khan, Khurram Ajaz (Transformations In Business & Economics, 2024)
The aim of this paper is to present the impact of significant factors that influence the attitudes of SMEs towards the social and environmental aspects of their sustainability. The research analyses the impact of three important areas which are HRM, CSR and financial management of SMEs. The empirical research to support the research objective was conducted in June 2022 through a questionnaire survey in Visegrad Four countries (V4 countries). SMEs were selected by random sampling method. Data collection was provided by an external agency using the Computer Assisted Web Interviewing (CAWI) method. The total number of respondents in this research was 1,398. The financial performance of the firm has the greatest influence on the formation of positive attitudes of SMEs towards social and environmental responsibility. This factor clearly dominated the attitudes of SMEs. The second most frequent factor was the knowledge of the most important aspects of a firm’s financial management which also significantly shapes SMEs’ social and environmental responsibility. Other factors that significantly shape SMEs’ attitudes towards social and environmental responsibility are the application of CSR in the firm’s activities and its perception as a tool for gaining competitive advantages in the market and SMEs’ belief that they can appropriately manage financial risks in the firm. The third group of factors can be classified as X2 and X6. Caring for employees and motivating them to innovate working practices and the belief that CSR enables the company to win new customers also shape SMEs’ responsible approach to social and environmental responsibility. Interestingly, the correct perception of human capital in a firm has minimal influence on shaping these attitudes. SMEs in the V4 countries also confirmed that investment in improving the skills of employees is a rare phenomenon.